Effects of Motor Training on Accuracy and Precision of Jaw and Finger Movements - Yinan Chen; Song Wu; Zhengting Tang; Jinglu Zhang; Lin Wang; Linfeng Yu; Kelun Wang; Peter Svensson (Neural Plasticity)
Objective. To compare the effects of training of jaw and finger movements with and without visual feedback on precision and accuracy. Method. Twenty healthy participants (10 men and 10 women; mean age 24.6±0.8 years) performed two tasks: a jaw open-close movement and a finger lifting task with and without visual feedback before and after 3-day training. Individually determined target positions for the jaw corresponded to 50% of the maximal jaw opening position, and a fixed target position of 20 mm was set for the finger. Movements were repeated 10 times each. The variability in the amplitude of the movements was expressed as percentage in relation to the target position (Daccu—accuracy) and as coefficient of variation (CVprec—precision). Result. Daccu and CVprec were significantly influenced by visual feedback (P=0.001 and P<0.001, respectively) and reduced after training jaw and finger movements (P<0.001). Daccu (P=0.004) and CVprec (P=0.019) were significantly different between jaw and finger movements. The relative changes in Daccu (P=0.017) and CVprec (P=0.027) were different from pretraining to posttraining between jaw and finger movements. Conclusion. The accuracy and precision of standardized jaw and finger movements are dependent on visual feedback and appears to improve more by training in the trigeminal system possibly reflecting significant neuroplasticity in motor control mechanisms.